Penile implants and other high risk practices in French Guiana's correctional facility: A cause for concern. - Marie-Claire Parriault; Amandine Chaponnay; Claire Cropet; Vincent About; Agathe Pastre; Roch Perusseau-Lambert; Mathieu Nacher; Florence Huber (PLoS ONE, 2019)
BACKGROUND:Prisoners in French Guiana, a French territory located in South America, have a HIV and hepatitis B prevalence of 4%. Body modifications such as penile implants, tattoos, and body piercings are common among detainees, increasing the risk of blood-borne virus transmission. METHODS:We conducted a cross-sectional randomised survey in which the primary objective was to estimate the prevalence of high risk 'bloody practices' (penile implants, tattoos, body piercings) in French Guiana's only correctional facility. The secondary objective was to describe the risk factors for penile implants, the procedures and motivations for insertion, the reported complications, their risk factors and adverse impact on condom use. RESULTS:Of the 221 male inmates interviewed, 19% had tattoos or body piercings while incarcerated, and 68% had penile implants, of which, 85% had been inserted inside the correctional facility. Addictive behaviors such as cannabis use and alcohol addiction (positive AUDIT-C score), early age at first sexual intercourse, and the number of incarcerations correlated positively with having inserted one or more penile implants while incarcerated. In contrast, having reported previous psychiatric hospitalizations and having a high knowledge score for HIV/AIDS and sexually transmitted infections (STIs) were negatively correlated with the insertion of penile implants while incarcerated. Penile implants were inserted in poor hygienic conditions, usually using the sharp lid of a canned food container, with 18% of early complications, mostly haemorrhage and edema. Condom use was negatively impacted for 52% of men with penile implants. CONCLUSIONS:Our results highlight the need for prevention interventions which should aim at increasing knowledge levels and at implementing comprehensive risk-reduction measures.